Descriptive Study Of Phonological Development In Acquiring English Pronounciation - Maulida Maulida; Santi Sari devi; Yani Yani (Universitas Palangka Raya, 2023)
This descriptive study aims to investigate the phonological development in acquiring English pronunciation among learners. The research focuses on understanding the process by which learners develop their pronunciation skills in English as a second language. The study employs qualitative research methods, involving data collection through recordings of learners' speech and interviews. The participants are English language learners from various linguistic backgrounds. The findings provide insights into the specific phonological challenges faced by learners and highlight the patterns and stages of their development in acquiring English pronunciation. The study contributes to the understanding of the factors influencing phonological acquisition and offers implications for language teaching and curriculum design.